ANALYSIS OF PEDOLOGICAL FACTORS AND USCS IN THE CONTACT AREA OF ĐAKOVO LOESS PLATEAU AND DILJ GORA, CROATIA - Hrvoje Heštera (Rudarsko-geološko-naftni Zbornik, 2020)
The pedological factors concerning the Unified Soil Classification System (USCS) in the contact area of Đakovo loess plateau and Dilj gora have been explored. The study was carried out to create a cross-country mobility map for vehicles. The spatial GIS analysis included soil units of Basic Soil Map (BSM) at a scale of 1:50000, which, according to the World Reference Base (WRB), contain within themselves the distribution of soil units, particle size distribution according to the United States Department of Agriculture (USDA) soil classification and organic content, as well as data from the Basic Geological Map (BGM) at a scale of 1:100000, together with the information on the original parent material from which the soils originate. Field sampling (72 samples) and laboratory sample analysis were performed according to the USCS. The samples were collected at the same locations (50 samples) as the profiles which had been extracted during the development of BSM to enable a comparison of the two classification systems. The analysis did not confirm a clear statistical connection between the USDA and USCS. The compatibility of BSM pedological units and low plasticity clays (CL) is clearly visible in all units, except for the units located on the alluvium. The presence of low plasticity clay (CL) and high plasticity clay (CH) has been confirmed in the stagnosols on the alluvium. By incorporating the geological basis into the spatial analysis, low plasticity clays were found to belong to the Quaternary source material, whereas high plasticity clays were formed on the parent substrate of Neogene age. Data analysis and cartographic representation of the results according to the Waterways Experiment Station (WES) Method of the cone index were obtained using fuzzy logic. The principles of fuzzy logic were used at the boundaries of pedological units due to the inability to define clear boundaries or the cessation of a particular type of soil’s presence.